Congenital Cutis Aplasia of the Lower Limbs. A Case Report and Literature Review - Aymeé Marrero Gil; Gretel Águila Calero; Laura Vázquez Pis (Revista Finlay, 2021)
The aplasia complexion congenital it is a pathology that a heterogeneous group of clinical present forms from the moment of the birth comprises. It is characterized for the absence of all the capes of the skin at the organism's some zones and his most frequent presentation is in the scalp, being rare in all fours. It can be of exogenous or genetic origin. His etiology consists fundamentally in a premature defect of differentiation of the embryo and it correlates multiple causes itself could have accompanied in some cases of malformations another levels. Several forms of treatment, conservative and surgical treatment exist. The intervention of a multi-disciplinary team for his satisfactory evolution becomes necessary. The complexion presents a case with aplasia itself congenital in both inferior members that is diagnosed just after the birth and that you receive medical and surgical treatment, obtentions proven to be satisfactory for the patient from the functional and esthetic point of view of all fours. You encounter this case because in a general way the aplasia the complexion has very low incidence for what the presentation of this report that the affection localized in the inferior members has proves to be important.